2013
DOI: 10.1016/j.astropartphys.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for observations of pulsars and pulsar wind nebulae with CTA

Abstract: The last few years have seen a revolution in very-high gamma-ray astronomy (VHE; E > 100 GeV) driven largely by a new generation of Cherenkov telescopes (namely the H.E.S.S. telescope array, the MAGIC and MAGIC-II large telescopes and the VERITAS telescope array). The Cherenkov Telescope Array (CTA) project foresees a factor of 5 to 10 improvement in sensitivity above 0.1 TeV, extending the accessible energy range to higher energies up to 100 TeV, in the Galactic cut-off regime, and down to a few tens GeV, cov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 54 publications
(100 reference statements)
3
32
0
Order By: Relevance
“…Despite the harder high-energy spectrum (γ = 3.0), a simulation of a 50 h observation of the Crab pulsar above 1 TeV also yields a marginal detection (S=4) because of the contamination from the bright point-like (in gamma-rays) Crab nebula. This result is consistent with the simu- lations presented by de Oña-Wilhelmi et al (2013). It also demonstrates an improvement of the CTA performance compared with the currently operating IACTs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Despite the harder high-energy spectrum (γ = 3.0), a simulation of a 50 h observation of the Crab pulsar above 1 TeV also yields a marginal detection (S=4) because of the contamination from the bright point-like (in gamma-rays) Crab nebula. This result is consistent with the simu- lations presented by de Oña-Wilhelmi et al (2013). It also demonstrates an improvement of the CTA performance compared with the currently operating IACTs.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the pulsars simulations, we also calculate independently CTA sensitivity curves for each pulsar, comparing them with results of the ctools analysis. Our results are compared with similar estimates reported in 1FHL (Ackermann et al 2013) and in de Oña-Wilhelmi et al (2013).…”
Section: He Fermi Pulsars With the Cherenkov Telescope Arraysupporting
confidence: 85%
See 1 more Smart Citation
“…MAGIC discovered the first VHE pulsar when it detected pulsed emission the Crab. VERITAS has shown that emission extends up to 400 GeV and MAGIC even reports pulsed emission beyond 1 TeV, as opposed to an exponential cutoff as might have been expected (see [24] and references within). HESS-II has reported pulsed emission from the Vela pulsar, but no indication of a VHE spectral extension yet.…”
Section: Pulsarsmentioning
confidence: 99%
“…VHE PWN are very extended (up to 1-2 • ) so their study will benefit from the wide field of view of CTA [24]. The large energy range covered by CTA will be crucial to understand cooling effects in the electron parent populations, including the resolution of internal structures and the possibility to disentangle between synchrotron or adiabatic losses.…”
Section: Pulsar Wind Nebulaementioning
confidence: 99%